Analisis Faktor-Faktor yang Memengaruhi Niat Pengguna Internet untuk Menggunakan Fungsi Single Sign On Google dengan Metode SEM (Structural Equation Modeling) - Lina Andreina; Ari Kusyanti; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Google is a company which provides email account. Email account is used for third-party service's registration. Nowadays, Google provides single sign on function. This function enables Internet users, use only one authentication process to obtain permission to access third-party's services. Single sign on process allows data sharing process from respective account (Google's Email) to the third-party. This process increases the risk of personal data loss. This research aims to determine the factors that affect Internet user's intention to use Google's single sign on, by using SEM (Structural Equation Modelling). In this research, there are 10 latent variables with 30 indicators. Those variable latent are Trust, Perceived Usefulness, Perceived Ease of Use, Behavioral Intention of Use, Risk, Security, and Privacy (Second order using IUIPC). This research collects 247 respondents, who have used Google's single sign on, through online questionnaire. The results shows,research model is Fit and the factors that affect Internet user's intention to use Google's single sign on are Perceived Usefulness and Risk